PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA NON FISIK TERHADAP KINERJA PEGAWAI PADA KECAMATAN PAMULANG - Dhamarrochman Dhamarrochman; Feb Amni Hayati (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Abstract. This study aims to determine the effect of work motivation and the non-physical work environment on employee performance at the Pamulang District Office. The research method used in this study is quantitative. The population of the study consisted of all employees, totaling 88 respondents.The results of the study show that Work Motivation (X1) affects Employee Performance (Y), as seen from the simple regression equation Y = 30.000 + 0.115X1. The correlation coefficient has a value of 0.232, which falls within the interval 0.200–0.399, indicating that the relationship between Work Motivation (X1) and Employee Performance (Y) is low. The coefficient of determination obtained was 0.017, which means that the Work Motivation variable (X1) influences Employee Performance (Y) by 17%, while the remaining 83% is influenced by other variables not examined in this study. The hypothesis test (t-test) shows that the calculated t-value is smaller than the t-table value (1.204 < 1.663).The Non-Physical Work Environment (X2) has a negative effect on Employee Performance (Y). The simple regression analysis produced the equation Y = 50.765 − 0.530X2. The correlation coefficient value is 0.366, which lies in the interval 0.200–0.399, indicating that the relationship between the Non-Physical Work Environment (X2) and Employee Performance (Y) is low. The coefficient of determination obtained was 0.134, meaning that the Non-Physical Work Environment variable (X2) affects Employee Performance (Y) by 13.4%, while the remaining 86.6% is influenced by other variables not examined. The t-test results show that the calculated t-value is greater than the t-table value (3.648 > 1.663).Work Motivation (X1) and the Non-Physical Work Environment (X2) simultaneously affect Employee Performance (Y), as evidenced by the multiple linear regression equation Y = 43.519 + 0.198X1 − 0.601X2. The correlation coefficient indicates that the relationship between work motivation and the non-physical work environment simultaneously with employee performance has a value of 0.425, which means that the dependent and independent variables have a moderate relationship. The coefficient of determination (R Square) obtained is 0.180, which indicates that 18% of the variation in Employee Performance (Y) is determined by the two independent variables, namely Work Motivation (X1) and the Non-Physical Work Environment (X2), while the remaining 82% is influenced by other variables not examined in this study. The results of the hypothesis test (F-test) show an F-value of 9.359 with a significance value of 0.000, indicating that Fcount > Ftable (9.359 > 3.104) and the significance value is 0.000 < 0.05. Keywords: Work Motivation, Non-Physical Work Environment, Employee Performance